An experimental investigation on the mechanical properties and chloride permeability of concrete with sea sand as fine aggregate - Dash, Sabita; Bhattacharyya, Sriman Kumar; Deb, Arghya (Journal of Structural Engineering, 2024)
The current paper is focused on the potential usage of sea sand in concrete. Sea sand was collected from two different sources, namely Puri sea shore Odisha, and Digha sea shore, West Bengal, India. Mechanical properties and resistance to chloride penetration of concrete comprising various combinations of natural river and sea sand, ranging from partial substitution in washed and unwashed conditions to 100% replacement with sea sand, were evaluated. The study revealed that, sea sand concrete gains early strength faster whereas the rate of gain in strength decreases with time. The 7 days strength of Puri beach unwashed sea sand is 46.52% higher whereas after 28 days of curing, attains about 22.74% lower strength than Reference Concrete (RC). On the other hand, though it gains less strength initially, concrete with washed sea sand from Puri reaches similar strength with RC at 28 days. The result differs with the percentage replacement for Digha beach sand. Rapid Chloride Penetration Test (RCPT) results indicated that the total charge that passes through the sea sand concrete decreases with age and the chloride resistance was not significantly impacted by the chloride ions from sea sand, at later stage.